2019
DOI: 10.3390/arts8030118
|View full text |Cite
|
Sign up to set email alerts
|

Circling Round Vitruvius, Linear Perspective, and the Design of Roman Wall Painting

Abstract: Many scholars believe that linear perspective existed in classical antiquity, but a fresh examination of two key texts in Vitruvius shows that 1.2.2 is about modularity and symmetria, while 7.Pr.11 describes shading (skiagraphia). Moreover, these new interpretations are firmly based on the classical understanding of optics and the history of painting (e.g., Pliny the Elder). A third text (Philostratus, Imagines 1.4.2) suggests that the design of Roman wall painting depends on concentric circles. Philostratus’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Regarding the transition from inside to outside, Throughout human history we have seen various attempts to visually overcome the confined spaces of walled rooms. In Roman wall paintings a recurring motif is the picturing of outdoor landscapes as if seen through a window or an opening in a wall, like in the preserved paintings from the Villa of P. Fannius Synistor at Boscoreale dated to 50-40 BC (Small, 2019). This "seeing through" solid surfaces exploits the 2D plane to achieve a visual extension of the 3D space.…”
Section: Liestøl Museums Artefacts and Cultural Heritage Sitesmentioning
confidence: 99%
“…Regarding the transition from inside to outside, Throughout human history we have seen various attempts to visually overcome the confined spaces of walled rooms. In Roman wall paintings a recurring motif is the picturing of outdoor landscapes as if seen through a window or an opening in a wall, like in the preserved paintings from the Villa of P. Fannius Synistor at Boscoreale dated to 50-40 BC (Small, 2019). This "seeing through" solid surfaces exploits the 2D plane to achieve a visual extension of the 3D space.…”
Section: Liestøl Museums Artefacts and Cultural Heritage Sitesmentioning
confidence: 99%
“…Recent research covers De Architectura's standing both in the humanities and in the sciences. Further to a publication on Vitruvius as an author [21], related studies cover a contemporary reading of the opening chapter of De Architectura [22], the literary significance of the treatise [23][24][25][26][27][28][29][30] and its raced-gendered narrative [31], the use of building materials and construction methods as media forming the identity of the Roman Empire [32], and Vitruvius's geographical system [33] and design (e.g., linear perspective [34], Roman temples [35], the Basilica at Fano [36,37] and acoustic vessels [38]). Studies related to the last of these themes include the geological analysis of tuff and travertine in stone masonry [39][40][41], mortar [42][43][44] and concrete technology [45][46][47], notably seawater concrete [48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…102-5). Yet the theory of vanishing vertical axis applied in the Roman context has been contested by a recent study by Small (2019), which suggested that concentric circles, grids, or a combination were more likely used for the design of Roman painted walls. The current study investigates, rather than painting techniques, the religious meaning the perspective potentially convey.…”
mentioning
confidence: 99%